2020
DOI: 10.1175/jtech-d-19-0210.1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Cloud Droplet Motion under Sound Wave Actions

Abstract: Sound waves have proven to be effective in promoting the interaction and aggregation of droplets. It is necessary to theoretically study the motion of particles in sound field to develop new acoustic technology for precipitation enhancement. In this paper, the motion of cloud droplets due to a traveling sound wave field emitted from the ground to the air is simulated using the motion equation of point particles. The force condition of the particles in the oscillating flow field is analysed. Meanwhile, the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…It was previously reported thatin the presence of a strong sound fieldmicroparticles undergo so-called acoustic agglomeration; i.e., their movements are affected in such a way that the microparticles approach one another. In fact, acoustic agglomeration is an effective way to remove dust, particles, and droplets by using generated sound waves. Both theoretical and experimental studies indicate that the sound waves with high sound pressure level (∼100 dB) and low frequency (<500 Hz) have a carrying effect on microparticles. ,,, In the present study involving ESI microdroplets, the effect was noticeable when the sound pressure level was above 100 dB and the frequency was below 400 Hz (cf. Figure S18).…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…It was previously reported thatin the presence of a strong sound fieldmicroparticles undergo so-called acoustic agglomeration; i.e., their movements are affected in such a way that the microparticles approach one another. In fact, acoustic agglomeration is an effective way to remove dust, particles, and droplets by using generated sound waves. Both theoretical and experimental studies indicate that the sound waves with high sound pressure level (∼100 dB) and low frequency (<500 Hz) have a carrying effect on microparticles. ,,, In the present study involving ESI microdroplets, the effect was noticeable when the sound pressure level was above 100 dB and the frequency was below 400 Hz (cf. Figure S18).…”
Section: Resultsmentioning
confidence: 61%
“…38−41 Both theoretical and experimental studies indicate that the sound waves with high sound pressure level (∼100 dB) and low frequency (<500 Hz) have a carrying effect on microparticles. 35,37,38,42 In the present study involving ESI microdroplets, the effect was noticeable when the sound pressure level was above 100 dB and the frequency was below 400 Hz (cf. Figure S18).…”
Section: ■ Results and Discussionmentioning
confidence: 62%
“…However, the droplet growth ratio is 3.60 at a frequency of 400 Hz, and the droplet growth ratio is only 1.49 at a frequency of 200 Hz. Moreover, the experimental results also show that the effect of the sound waves on the droplet growth ratio gradually decreases for higher frequencies than 500 Hz [25]. That is, high-frequency sound waves are not conducive to the applications of fog elimination or rainfall.…”
Section: Influence Of Frequencymentioning
confidence: 96%
“…Tulaikova T V et al 71 further explored the theoretical underpinnings and practicability of acoustic methods in enhancing rainfall. Li 72 et al utilized the point particle motion equation to simulate cloud droplets' movement induced by ground-emitted traveling acoustic waves, examining the influence of droplet size, acoustic frequency, and sound pressure level on droplet velocity and displacement. For droplets measuring 50 μm, the conditions for significant displacement fluctuations were identified as 10 Hz and 88.2 dB.…”
Section: Application Of Acoustic Agglomerationmentioning
confidence: 99%